2020
DOI: 10.1101/2020.02.29.971309
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genomic diversity ofEscherichia coliisolates from non-human primates in the Gambia

Abstract: 8Increasing contact between humans and non-human primates provides an opportunity for the 1 9 transfer of potential pathogens or antimicrobial resistance between host species. We have 2 0 investigated genomic diversity, and antimicrobial resistance in Escherichia coli isolates from 2 1 four species of non-human primate in the Gambia: Papio papio (n=22), Chlorocebus sabaeus 2 2 (n=14), Piliocolobus badius (n=6) and Erythrocebus patas (n=1). We performed Illumina 2 3whole-genome sequencing on 101 isolates from 4… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 76 publications
0
9
0
Order By: Relevance
“…Co-colonization of single hosts with multiple strains may facilitate the spread of AMR-and virulence-associated genes from resistant strains to other bacteria via both horizontal and vertical gene transfer [75]. A high co-colonization rate of E. coli has been described in humans [76,77] and in non-human primates [32], involving pathogenic strains of E. coli. Recently, Li et al reported three to nine sequence types of colistin-resistant E. coli to co-exist within a single broiler chicken [30].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Co-colonization of single hosts with multiple strains may facilitate the spread of AMR-and virulence-associated genes from resistant strains to other bacteria via both horizontal and vertical gene transfer [75]. A high co-colonization rate of E. coli has been described in humans [76,77] and in non-human primates [32], involving pathogenic strains of E. coli. Recently, Li et al reported three to nine sequence types of colistin-resistant E. coli to co-exist within a single broiler chicken [30].…”
Section: Discussionmentioning
confidence: 99%
“…Genomic DNA was extracted from overnight broth cultures prepared from each single colony sub-culture using an in-house 96-well plate lysate method as described previously [32]. The DNA was eluted in Tris/Cl (pH, 8.0) and quantified using the Qubit high-sensitivity DNA assay kit (Invitrogen, MA, USA).…”
Section: Genomic Dna Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Broth cultures were prepared from pure, fresh cultures of each colony-pick in 1 ml Luria-Bertani broth and incubated overnight to attain between 10 9 -10 10 cfu per ml. Genomic DNA was then extracted from the overnight broth cultures using the lysate method described in (33). The eluted DNA was quantified by the Qubit high sensitivity DNA assay kit (Invitrogen, MA, USA) and sequenced on the Illumina NextSeq 500 instrument (Illumina, San Diego, CA) as described previously (34).…”
Section: Genomic Dna Extraction and Genome Sequencingmentioning
confidence: 99%
“…Similarly, ST681 strains were found nearly worldwide in animals (wild boars, non-human primates) and among isolates causing human ExPEC infections, including UTI [56][57][58][59] . Furthermore, besides reports on UTI caused by ST569, this lineage could have possible food and…”
mentioning
confidence: 99%